Alexithymic Traits and Hair Cortisol Concentrations in Pregnant Women - Kajanoja, Jani; Karukivi, Max; Mustonen, Paula; Scheinin, Noora M.; Kortesluoma, Susanna; Rodrigues, Ana João; Karlsson, Hasse; Karlsson, Linnea (Frontiers in Psychiatry, 2020)
Introduction: Alexithymia, a personality construct characterized by difficulties in identifying and expressing emotions, and an externally oriented thinking style, has been associated with a number of stress-related disorders, and physiological markers of stress. We examined the relationships of alexithymia and hair cortisol concentrations (HCC), a measure of long-term cortisol levels, in pregnant women. Methods: Participants were 130 women from the FinnBrain birth cohort study. Alexithymia was measured with the Toronto Alexithymia Scale (TAS-20). Analysis of covariance and regression analyses were used to assess the associations between alexithymia and HCC. Educational level, current depressive symptoms, and body mass index (BMI) were applied as covariates. Results: In the adjusted analyses, individuals with moderate to high alexithymic traits had significantly higher HCC (F=5.11, partial η² 0.040, p=0.026) compared to non-alexithymics. Regression analyses in the whole sample revealed that, of the individual dimensions of alexithymia, Difficulty Identifying Feelings (DIF) was associated with HCC (β=0.187, t=2.064, p=0.041). Conclusions: Alexithymia, and especially its dimension DIF were associated with higher HCC, and therefore may be linked to increased chronic physiological stress. Implications for pregnancy outcomes and infant development are discussed.